1995
DOI: 10.1086/175480
|View full text |Cite
|
Sign up to set email alerts
|

Deviations from chemical equilibrium due to spin-down as an internal heat source in neutron stars

Abstract: The core of a neutron star contains several species of particles, whose relative equilibrium concentrations are determined by the local density. As the star spins down, its centrifugal force decreases continuously, and the star contracts. The density of any given uid element increases, changing its chemical equilibrium state. The relaxation towards the new equilibrium takes a nite time, so the matter is not quite in chemical equilibrium, and energy is stored that can be released by reactions. For a neutron sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
241
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(247 citation statements)
references
References 28 publications
4
241
1
1
Order By: Relevance
“…These estimates show that τ cool is of the same order of magnitude as τ rel for both cases of the slow and fast cooling, with τ rel being several times shorter. Using this fact Reisenegger (1995) concluded that the beta relaxation occurs much faster than the cooling. From our point of view, the difference by a factor of several is not decisive and the non-equilibrium state may persist for some time, i.e, the value of ξ may decrease slowly as the cooling proceeds.…”
Section: Non-equilibrium Urca Processesmentioning
confidence: 98%
See 4 more Smart Citations
“…These estimates show that τ cool is of the same order of magnitude as τ rel for both cases of the slow and fast cooling, with τ rel being several times shorter. Using this fact Reisenegger (1995) concluded that the beta relaxation occurs much faster than the cooling. From our point of view, the difference by a factor of several is not decisive and the non-equilibrium state may persist for some time, i.e, the value of ξ may decrease slowly as the cooling proceeds.…”
Section: Non-equilibrium Urca Processesmentioning
confidence: 98%
“…It is much longer than the typical timescale ∼ 10 −3 s, corresponding to the local compression of matter during the collapse of a neutron star into the black hole (Gourgoulhon and Haensel 1993) or to the radial pulsations of the neutron star. In sufficiently old pulsars, τ rel can also be much longer than the timescale of the local compression of matter, implied by the slowing-down of pulsar rotation (Reisenegger 1995). In all these cases, one has to consider the Urca processes in neutron star matter out of beta equilibrium (Haensel 1992, Reisenegger 1995.…”
Section: Non-equilibrium Urca Processesmentioning
confidence: 99%
See 3 more Smart Citations